Efektivitas Model Problem Bassed Learning (PBL) Terhadap Peningkatan Hasil Belajar Bola Voli Pada SDN 1 Labuan Pandan - Zhean Sengga Pradipthama; Ali Muhaimin; Lukman Lukman (Universitas Hamzanwadi, 2026)
The basic skills of passing the volleyball ball among fourth-grade students at SDN 1 Labuan Pandan are still low, as indicated by an initial learning completeness rate of only 37.5%. The low mastery of this technique is thought to be due to conventional teaching methods that do not sufficiently involve students in problem solving. This study aims to analyze the effectiveness of applying the Problem-Based Learning (PBL) model in improving learning outcomes in underhand passing in volleyball in terms of cognitive and psychomotor aspects. This study used the Classroom Action Research (CAR) method, which was carried out in two cycles, with each cycle consisting of the planning, implementation, observation, and reflection stages. The research subjects were 24 fourth-grade students. Data were collected through cognitive tests, psychomotor performance assessments, and observations of the learning process, then analyzed descriptively and quantitatively. The results showed a significant improvement in learning outcomes. Classical mastery in the cognitive aspect increased from 37.5% (pre-cycle) to 58.3% (cycle I) and 91.6% (cycle II). In the psychomotor aspect, mastery increased from 45.8% to 58.3% (cycle I) and 91.6% (cycle II). It was concluded that the PBL model was effective in improving volleyball learning outcomes because it encouraged students to be actively involved in analyzing movement problems and practicing their solutions contextually.